Resistencia indígena y la evolución de fronteras en el Río Chinchipe, Alto Marañon - Girot, Pascal Olivier (1990)
Analysis of the economy and political history of Río Chinchipe Valley, and the reasons why this has been an area of political dispute. The Jíbaros`s bellicose resistence created especial conditions for the social relationship of production in this frontier area.